Time series of ice nuclei concentration at Cape Verde - André Welti; Konrad Müller; Zoë L Fleming; Frank Stratmann (PANGAEA, 2018)
Cumulative ice nuclei concentration as function of temperature determined using filter samples collected at the Cape Verde Atmospheric Observatory. Samples cover the year 2009-2013. Measurements cover the temperature range 0°C to -20°C. Additional concentration measurements obtained with the SPIN CFDC from an intense campaign in Jan.-Feb. 2016 at the Cape Verde Atmospheric Observatory complement the dataset at temperatures below -24°C.
Supplement to: Welti, A et al. (2018): Concentration and variability of ice nuclei in the subtropical maritime boundary layer. Atmospheric Chemistry and Physics, 18(8), 5307-5320, https://doi.org/10.5194/acp-18-5307-2018